Pelatihan Manajemen SDM dan Literasi Keuangan Bagi Santri dan Siswa di Lingkungan Pondok Pesantren Al-Muqriyah - Aldo Rizki Pratama; Fatma Rahayu Ningsih; Siti Ambarwati (CV. ITTC INDONESIA, 2026)
This Community Service Program (PKM) aims to improve the understanding and readiness of santri and vocational high school (SMK) students in human resource management and financial literacy as preparation for entering the workforce and social life. The program was conducted at Pondok Pesantren Al-Muqriyah using an educational and participatory approach through lectures, discussions, and question-and-answer sessions. The training materials covered basic concepts of human resource management, self-management, discipline, responsibility, as well as simple financial literacy such as financial planning, income and expense recording, and financial control. The results of the program indicate an increase in participants' understanding of the importance of human resource management and financial literacy, as reflected in their active participation and enthusiasm during the activities. This program is expected to help santri and SMK students become more independent, disciplined, and economically responsible individuals in the future.